Potentially avoidable hospitalisations of German nursing home patients?: a cross-sectional study on utilisation patterns and potential consequences for healthcare - Leutgeb, Rüdiger; Berger, Sarah; Szecsenyi, Joachim; Laux, Gunter (BMJ open, 2019)
Objectives: Demand for nursing home (NH) care is soaring due to gains in life expectancy and people living longer with chronic illness and disability. This is dovetailing with workforce shortages across the healthcare profession. Access to timely and appropriate medical care for NH residents is becoming increasingly challenging and can result in potentially avoidable hospitalisations (PAHs). In light of these factors, we analysed PAHs comparing NH patients with non-NH patients. Design: Cross-sectional study with claims data from 2015 supplied by a large German health insurance company within the federal state of Baden-Wuerttemberg. Setting: One-year observation of hospitalisation patterns for NH and non-NH patients. Participants: 3 872 245 of the 10.5million inhabitants of Baden-Wuerttemberg were covered. Methods: Patient data about hospitalisation date, sex, age, nationality, level of care and diagnoses were available. PAHs were defined based on international classification of diseases (ICD-10) diagnoses belonging to ambulatory care sensitive conditions (ACSCs). Adjusted ORs for PAHs for NH patients in comparison with non-NH patients were calculated with multivariable regression models. Results: Of the 933 242 hospitalisations in 2015, there were 23 982 for 13 478 NH patients and 909 260 for 560 998 non-NH patients. Mean age of hospitalised NH patients and level of care were significantly higher than those of non-NH patients. 6449 PAHs (29.6%) for NH patients and 136 543 PAHs (15.02%) for non-NH patients were identified. The adjusted OR for PAHs was significantly heightened for NH patients in comparison with non-NH patients (OR: 1.22, CI (1.18 to 1.26), p<0.0001). Moreover, we could observe that more than 90% of PAHs with ACSCs were unplanned hospitalisations (UHs). Conclusions: Large numbers of PAHs for NH patients calls for improved coordination of medical care, especially general practitioner service provision. Introduction of targeted training programmes for physicians and NH staff on health problem management for NH patients could perhaps contribute to reduction of PAHs, predominantly UHs.